Kekeliruan Hakim dalam Memutus Perkara Penipuan pada Pangadilan Negeri Sidoarjo - Agata, Anelia Dewi; Purwaningsih, Sri Budi (Indonesian Journal Publisher, 2024)
This study aims to determine whether there are elements of fraud in the case contained in Decision Number 115/Pid.B/2021/PN.SDA. This research is based on the reality related to business in the housing industry which is currently growing rapidly but so many default cases are carried out by the developers themselves. As in the case that I am currently investigating, namely Decision Number 115/Pid.B/2021/PN.SDA. The method used in this study is a normative legal research method using a statutory approach by using primary legal materials consisting of statutory regulations and secondary legal materials obtained from several books, journals, and articles. The results of the study conclude that, there is a decision by the Panel of Judges in deciding the case on Decision Number 115/Pid.B/2021/PN.SDA because the elements that cannot be submitted to. Based on the comparison between the actions taken with the elements of error in the default, it was stated that as the director of PT. A has committed an act of default for not carrying out the performance according to what has been agreed with the Buyer as a victim in the sale and purchase of a residential house.